EDUKASI PENCEGAHAN VIRUS COVID 19 MELALUI PEMBUATAN MASKER DAN DISINFEKTAN BAGI PENGUNJUNG PUSKESMAS BIARO DI KECAMATAN IV ANGKEK KABUPATEN AGAM - Fitriyani Fitriyani; Novia Wirna Putri; Septia Pristi Rahmah; Sherlyna Narkotopa; Elsa Aprillia; Ulfah Winanda Putri (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
The main cause of the increasing number of Covid 19 virus case, both the public and medical personnel, is a lack of concern in taking preventive action. Many people do not use masks when they are outside and not maintain personal hygiene and proper living environment. Most of their reasons were limited of masks, the high price of masks and antiseptics cleaning fluids, and the cloth masks on market were not standard. Puskesmas Biaro is one of the referral health center for Covid 19 patients. So that, this place is very vulnerable to being a place of virus transmission. But in fact, there are many visitors who don't use masks properly, never use the antiseptic to cleaned their houses or any objects that were good at attaching virus. The purpose of this activity was to increase community knowledge, especially for health care visitors to be able to make their own masks and disinfectant at home as a step to break the transmission chain of the Covid 19 virus. The education method was direct counseling. Based on the results of the pretest and post-test, there was a significant difference between the level of participants' knowledge before and after education. Then, based on participants monitoring were found 5 from 7 participants had applied the results of education in their daily lives. In conclusion, this educational activity was very useful, provided the easy and inexpensive solutions, and could be done directly by the participants in their home.